Interpersonal Intervensi dalam Pencegahan Kanker Serviks Perempuan Usia Subur - Anis Ardiyanti; Laura Khattrine Noviyanti; Nella Vallen Ika Puspita (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstract Cervical cancer is one of the most common types of cancer experienced by women, but it is not accompanied by screening rates. Based on data, the prevalence of IVA testing since the Covid-19 pandemic until now is relatively low compared to the population. The aim of this research is to increase the prevention of cervical cancer and improve the quality of life of women of childbearing age and their partners. The design of this research is quantitative research using Quasi-Experimental with Pretest-Posttest Design and qualitative with a phenomenological approach. This research was conducted involving 62 female respondents of childbearing age and their husbands to provide education, peer sharing about cervical cancer prevention and exploration was carried out with 12 participants. The results of the quantitative research are that there is an interpersonal influence of intervention on Quality of Life, Situational Influence, Husband's Support, Attitudes related to Activities, Prevention Behavior, Self Efficacy, Perceived Benefits of Action, Culture, and Perceived Health Status. The results of the qualitative research revealed 3 themes, including: Cervical cancer is a preventable disease, husband's support is very important for wives, and education and peer sharing are beneficial for couples of childbearing age. Most respondents stated that this education and sharing was very useful considering that it was not only women who carried out prevention but involved their partners because this disease was caused by the behavior of women of childbearing age and their partners. Abstrak Kanker serviks merupakan salah satu jenis kanker terbanyak yang dialami oleh perempuan, namun tidak dibarengi dengan angka screeningnya. Berdasarkan data, prevalensi IVA tes sejak pandemi Covid-19 hingga sekarang tergolong rendah dibandingkan dengan jumlah penduduk. Tujuan penelitian ini yaitu meningkatkan pencegahan kanker serviks serta meningkatkan kualitas hidup perempuan usia subur dan pasangannya. Desain penelitian ini yaitu penelitian kuantitatif dengan menggunakan Quasi-Eksperimental dengan Pretest-Posttest Design dan kualitatif dengan pendekatan fenomenologi. Penelitian ini dilakukan dengan melibatkan 62 responden perempuan usia subur beserta suami untuk diberikan edukasi, sharing sebaya tentang pencegahan kanker serviks dan dilakukan ekplorasi terhadap 12 partisipan. Hasil penelitian kuantitatif yaitu terdapat pengaruh interpersonal intervensi terhadap kualitas hidup, pengaruh situasional, dukungan suami, sikap yang berhubungan dengan aktivitas, perilaku pencegahan, self efficacy, manfaat tindakan yang dirasakan, budaya, dan status kesehatan yang dirasakan. Hasil penelitian kualitatif didapatkan 3 tema antara lain: Kanker serviks penyakit yang dapat dicegah, Dukungan suami sangat penting untuk istri, serta Edukasi dan sharing sebaya bermanfaat untuk pasangan usia subur. Sebagian besar responden menyatakan edukasi dan sharing ini sangat bermanfaat mengingat tidak hanya perempuan saja yang melakukan pencegahan namun melibatkan pasangan karena penyakit ini diakibatkan oleh perilaku perempuan usia subur dan pasangannya.